Household Expenditure on Diarrhea Treatment among Under Five Children in Godawari Municipality of Nepal - Shrestha, Marina Vaidya; Adhikari, Shiva Raj; Manandhar, Naresh; Choulagai, Bishnu P; Pradhan, Bandana (Journal of Nepal Health Research Council, 2019)
Background: Diarrheal disease is a global public health problem. In Nepal, diarrhea is still the leading cause of waterborne disease, which constitutes 48% among all hospitalized disease cases who come to health center for treatment. Despite low treatment cost of diarrhea, out-of-pocket expenditure required at the time of treatment is a major barrier to seek health care. This study, therefore, aims to explore household expenditure for the diarrheal treatment in under five children and its financial burden in households.Methods: A community based cross sectional study was carried out in 14 wards of Godawari Municipality among under five children with diarrhea from June 2018 to September 2018. We conducted financial burden survey among 371 household with diarrhea cases.Results: Prevalence rate of diarrhea was found 50% among under five children. The average out-of-pocket expenditure was NRs 568.62 (US $5.06) per episode for diarrhea treatment. The total average direct cost for diarrheal treatment was NRs 183.58 (US $1.63). The two major cost driver during each episode were loss of wage by parents NRs 360.97 (US $3.21) and medicine costs NRs 114.15 (US $1.01). Conclusions: The Diarrheal prevalence rate in the study area was found higher than the National. The indirect cost of each diarrheal episode is more than three times of the direct cost.Keywords: Cost of illness; diarrhea; out of pocket expenditure; under five children.